Risks of pressure injury: application of the Braden Scale in intensive care (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
To identify, through the application of the Braden Scale, the risk of patients admitted developing pressure injuries (PI) and to verify the nursing care provided to prevent the incidence of these injuries in patients of an Intensive Care Unit (ICU) in the Base Hospital of the Distrito Federal. Method: Descriptive, quantitative and cross-sectional study. The study site was the Neurotrauma ICU of the Base Hospital of the Distrito Federal. Data were collected through the application of the Braden Scale within 72 hours of patient admission. A total of 96 individuals participated in the study. Results: The results showed that from the risk evaluation, the index that had the highest percentage in the subscale was activity, followed by the friction/ shear and mobility subscales. Conclusion: The research showed that all patients hospitalized at the unit presented some risk, whether low, moderate or high, to develop PI.